Identifikasi Senyawa Metabolit Sekunder Ekstrak Daun Bintaro (Cerbera manghas L.) Dengan Pelarut Etanol 70%, Aseton dan n-Hexan - Ahlan Sangkal; Rahmat Ismail; Nurfatima S. Marasabessy (Universitas Muhamadiyah Manado, 2020)
Bintaro (Cerbera manghas L.) is widely used as an analgesic, anticonvulsant, cardiotonic, and hypotensive activity. In Thailand bintaro is used as traditional medicine such as bark used as an antipyretic, laxative and in the treatment of dysuria. The flower part is applied to treat hemorrhoids. Secondary metabolites are chemical compounds contained in plants that can be drawn by a suitable solvent through extraction methods. The purpose of this study was to determine the content of secondary metabolites contained in bintaro leaf extract using ethanol, acetone, and n-Hexan solvents based on phytochemical screening. This research was carried out through two stages, namely extraction using maceration method using ethanol, acetone, n-Hexan and phytochemical screening solvents consisting of screening alkaloids, terpenoids, flavonoids, steroids, saponins, and tannins. The results showed that the bintaro leaf ethanol extract positively contained flavonoids, saponins, and tannins. The acetone extract of bintaro leaves positively contains, saponins and tannins. N-hexan daun bintaro extract positively contained steroids and alkaloids in testing with Dragendorft reagents, and was positive for Wagner reagents and negative for testing with Mayer reagents